Spokój czy smutek? Koncepcja starości w pismach Marka Tulliusza Cycerona - Kowalski, Henryk (Vox Patrum, 2011)
One of the great authorities in the antiquity who wrote about old age was Marcus Tullius Cicero, the author of „Cato Maior De senectute [Cato the Elder on Old Age]”. The famous orator wrote this work in 44 BCE and dedicated it to his friend Atticus. The author himself was almost 62 years old at that time, and Atticus 65. Cicero wrote the work in a dialogue form, setting the action in 150 BCE, the speakers being Marcus Porcius Cato the Elder, who in this case presented the views of Cicero, Publius Cornelius Scipio the Younger and Gaius Laelius Sapiens. Cicero followed the example of a Greek treatise on old age, probably written by a third-century BCE Peripatetic philosopher, Aristo of Ceos. The concept of the presentation of the treatise is based on comparison of two different views on old age. In one, sorrow and anxiety are visible. Through Cato’s words, Cicero names four reasons why people regard old age as an unhappy period of life: a). it moves us away from active life; b). it weakens physical strength, c). it deprives us of all sensual pleasures, d). it is close to death. The other view, represented by Cato, disproves the objections against old age, recommending calmness, activity, and moderation. Interestingly enough, apart from philosophical or medical arguments, Cicero also refers to political, religious, social and cultural aspects. The apologia for old age presented by Cicero was not always reflected in the reality. Roman sources, especially legal documents, inform about attempted suicide or euthanasia by the elderly. The fundamental reason was the condition of health and physical pain as well as mental illnesses, but the direct motive associated with old age was taedium vitae – weariness of life.